Major Trends in Oral Historiography in Mainland Tanzania, 1960s to the Present: A Review of Published Sources - Onyiego, Albertus K (Zamani: A Journal of African Historical Studies, 2024)
This article examines the role of oral methodology in reconstructing historical knowledge in Mainland Tanzania over the last six decades. Although greater attention is paid to the period from the 1960s onwards, efforts have been made to illuminate on the use of oral methodology in the period before. The article is organised into four temporal sections, each representing a distinct phase of oral methodology. The first section explores the role of oral methodology before independence. It will be noticed that the gradual use of oral sources in the writing of history in Mainland Tanzania started way back during German and British colonial periods. However, the early post-colonial period, notably the 1960s and the early 1970s, is considered the most effective and productive phases as far as oral methodology in Mainland Tanzania is concerned. Unlike the preceding phase whereby the practitioners in this field were amateur historians, the early post-colonial period witnessed the onset of the first generation of trained historians. The third section covers the transitional period, from the mid-1970s through the 1980s, in which the use of oral methodology slightly declined compared to the previous periods. The last section reflects on theoretical and methodological developments that took place in the post-Ujamaa period, starting from the early 1990s into the 2000s. This article is based on library research conducted between 2010 and 2023 at the University of Iowa in the United States and University of Dar es Salaam in Tanzania.